Managing the information systems in the industrial domain - Jaime Campos (Cogent Business & Management, 2016)
The purpose of the paper is to understand the developments of the Information Systems (IS) and Information technology, i.e. Information and Communication Technologies (ICTs) in the area of Condition Monitoring and Maintenance, especially e-maintenance. Therefore, the paper goes through and categorises the literature findings with the support of two models, i.e. the three era and the IS capability models to analyse and understand the maturity of the ICTs in the domain. The result shows that many researchers are working with software applications that are in the data processing era, which is highly important for the technologies and then the management of IS era. Conversely, both in the Management Information Systems and the Strategic Thinking era fewer findings have been made so far. Further on, in the fourth era, named the Information System (IS) capability, the research findings are mostly at the rudimentary stage. The implementation of Web technologies, such as the Web 2.0, i.e. Social media technologies, can facilitate the learning aspects in the maintenance department as well as collaboration between employees, which are important aspects of the last era, i.e. in the IS capability era. The paper highlights interesting organisational as well as ICT aspects that should be considered when planning, developing and implementing the e-maintenance IS.
Keywords: 650